The Mediating Role of Risk Perception in the Effect of Information Literacy on Students’ Disaster Preparedness - Nisye Frisca Andini; Riki Wanda Putra; M Fitriansyah Aldebaran (Universitas Negeri Medan, 2026)
This study examines how information literacy influences students’ disaster preparedness by incorporating risk perception as a mediating variable. Disaster-prone higher education environments require strong information comprehension skills to support readiness against potential hazards. The research involved 184 students from Merchant Marine Polytechnic of West Sumatra and STKIP Ahlussunnah, selected using purposive sampling. quantitative survey design approach was applied using SEM-PLS path analysis to evaluate direct and indirect effects. The results show that information literacy significantly influences disaster preparedness through an indirect effect mediated by risk perception (β = 0.205; p = 0.000). This finding highlights that risk perception strengthens the translation of information literacy into concrete preparedness actions. Practically, institutions should design information literacy programs that enhance not only access to technical data but als4o students’ awareness and appraisal of disaster risks. This study is limited by its focus on two campuses in a specific geographic area, suggesting the need for broader comparative studies. Overall, the research confirms that incorporating psychological components such as risk perception is essential for optimizing disaster preparedness strategies among university students.